Drought tolerance screening of maize accessions at early growth stage in the mid-hills of Nepal - Anubhav Tripathi; Rashmi Poudel; Reema Gurung; Unisha Ghimire; Mamata Pandey; Bishnu Prasad Kandel; Bal Krishna Joshi (Cogent Food & Agriculture, 2024)
Drought severely affects maize growth and productivity, making the identification of tolerant genotypes essential, especially in local maize. Therefore, a greenhouse pot experiment was conducted in Sundarbazar, Lamjung, from February to April using 30 local maize accessions under irrigated and drought conditions in a completely randomized block design to study nine vegetative traits and screen drought tolerance for upcoming breeding programs. Accession NGRC05570 showed relative tolerance to root length and number, NGRC05586 to shoot length, NGRC05589 to root-to-shoot ratio, NGRC05591 to moisture content in roots, NGRC05578 to moisture in shoot and relative water content (RWC), NGRC05561 to root volume and NGRC05573 to normalized difference vegetation index (NDVI). Accession NGRC05571, although lacking singular dominance in traits, exhibited an overall tolerance for NDVI, root-to-shoot ratio, root number, root length and RWC. Corelation analysis between shoot moisture content and shoot length showed a significant negative correlation under drought (−0.38) but a significant positive correlation under irrigation (0.38). Similarly, a significant negative correlation between the root-to-shoot ratio and shoot moisture content was observed under drought (−0.62) but not under irrigation. The possibility of accession NGRC05571, collected from Surkhet, being used in upcoming breeding studies has been seen, but a study on its ability to tolerate reproductive drought would be more insightful.